Third Party Funds as Moderating Variables of Liquidity Level of Sharia Commercial Banks - Wahidatun Nafiah Alfarda; Muhammad Afif An Nawawi; Mohammad As’adur Rofiq; Rizky Intan Syafitri (Indonesian Economic Review, 2023)
This study aims to examine the effect of BI 7-days (reverse) repo rate, sukuk, Bank Indonesia sharia certificates on the level of liquidity with third party funds as a moderating variable. The population in this study is all Islamic Commercial Banks in Indonesia. The sample in this study is the financial statements of Islamic banking statistics registered by OJK with 55 samples from June 2016-December 2020. The analytical technique of this study uses moderated regression analysis (MRA). The results of this study indicate that TPF can moderate the effect of the BI 7-days (reverse) repo rate and sukuk on FDR, but cannot moderate the effect of Bank Indonesia sharia certificates on FDR. Other results show that the BI 7-days (reverse) repo rate has a negative and significant effect on FDR, sukuk has a positive and significant effect on FDR and Bank Indonesia sharia certificates have a positive and significant effect on FDR.